ANALISIS UNSUR HARA PUPUK ORGANIK KOTORAN TERNAK DAN TANAH PROGAM GESEKU KABUPATEN BLORA - Wibawanti, Jeki Mediantari Wahyu; Ramadhan, Nunik Iriyanti; Marahendra, Wawan Dedi; Nafiah, Khittatun; Wibowo, Eryan Ari; Pamungkas, Sapto (AGRICA, 2025)
Agricultural land has been experiencing a decline in fertility due to the continuous and unbalanced use of chemical fertilizers, which negatively affects soil conditions and the surrounding environment. Organic fertilizers offer an environmentally friendly and sustainable alternative. One of the primary sources of organic fertilizer is livestock manure, which is utilized through the GESEKU program (Gerakan Sejuta Kotak Umat). This study aims to analyze the nutrient content of livestock manure-based organic fertilizer and the soil nutrient status following its application under the GESEKU program. This research method was carried out by purposive sampling, collecting soil samples from agricultural fields that had received organic fertilizer applications in eight districts across Blora Regency. The results showed that the fertilizer had a pH range of 7.02–8.99, nitrogen content of 2.17–2.94%, and organic carbon content between 15.00–32.60%. Total nitrogen content in the soil was categorized as moderate (0.22–0.33%). Available phosphorus ranged from low to very high (12.89–45.13 ppm), while exchangeable potassium was categorized as low to moderate (0.27–0.45 me/100g). The soil’s organic carbon content was classified as very low to low (0.54–1.66%). Based on the findings, it can be concluded that the soil in the sampled locations remains in an optimum condition for rice cultivation, indicating that the use of organic fertilizer from the GESEKU program contributes positively to maintaining soil fertility